PERBANDINGAN INHIBISI BERBAGAI EKSTRAK TUMBUHAN DAN VITAMIN C PADA FOTODEGRADASI TIROSIN YANG DIINDUKSI KETOPROFEN DAN KANDUNGAN FENOLIK TOTALNYA - Tatang Irianti; Nanang Fakhrudin; Efendi Efendi; Sigit Hartomo; Siluh Putu Yuni Astuti; Ratih Anggar Kusumaningtyas; Argandita Meiftasari (Faculty of Pharmacy, Universitas Gadjah Mada, 2016)
Antioxidant is known to inhibit free radical reaction. Tyrosine photodegradation can be caused by radical reaction. Nowadays, plant with antioxidants are widely used to inhibit free radical reaction. Study of inhibition of photodegradation used four groups. Those groups are: P1 consisted of 2mL tyrosine 0,05 %; P2 consisted of 2 mL tyrosine 0,05 %, and 600 μL Rhetoflam (topical ketoprofen) 1 %; P3 consisted of 2 mL tyrosine 0,05 %, 60μL Rhetoflam 1 %, and 100 μL tea leaf water ekstract 0,15 %; P4 consisted of 2 mL tyrosine 0,05 %, 600 μL Rhetoflam 1 %, and 100 μL mahkota dewa fruit water ekstract 0,15 %; P5 consisted of 2 mL tyrosine 0,05 %, 600 μL Rhetoflam 1 %, and 100 μL finger root etanolic ekstract 0,15 %; P6 consisted of 2 mL tyrosine 0,05 %, 600 μL Rhetoflam 1 %, and 100 μL vitamin C 0,15 %; each group is added with aquadest up to 5,0 mL and illuminated with mercuric lamp for four hours. Level of remaining tyrosine was measured with visible spectrophotometric method. We used ANOVA to analyse the data with convidence level of 0,95 and then continued by Tukey (HSD). Follin-Ciocalteu method with galic acid calibration curve was used to determine total phenolic level. The level of total phenolic of tea leaf aquoeus extract, mahkota dewa fruit aquoeus extract, fingerroot ethanolic extract were 29.64±0.86 %; 8.29 % 0.27 %; and 7.11 %, 0.15 %, respectively. Our investigation also found gallic acid equivalent (GAE) with the inhibition activity of 4.03; 1.58; and 2.09 and they were bigger than Vitamin C with the same concentration of 0.15 %.